2015
DOI: 10.1016/j.landusepol.2015.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Oil palm boom and land-use dynamics in Indonesia: The role of policies and socioeconomic factors

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
179
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(189 citation statements)
references
References 44 publications
(42 reference statements)
3
179
1
6
Order By: Relevance
“…It may be noted that the initial diffusion of oil palm in Jambi was mainly related to government supported smallholder schemes, in which farmers operated under contractual ties with large scale companies (Zen et al, 2006). More recently, smallholders took up oil palm independently and sporadically, without any government or private sector support Gatto et al, 2014). Irrespective of whether the smallholder adoption was sporadic or supported, oil palm was a novel crop and a livelihood option in the context of smallholder agriculture.…”
Section: Potential Impact Pathways Of Oil Palm Adoptionmentioning
confidence: 99%
“…It may be noted that the initial diffusion of oil palm in Jambi was mainly related to government supported smallholder schemes, in which farmers operated under contractual ties with large scale companies (Zen et al, 2006). More recently, smallholders took up oil palm independently and sporadically, without any government or private sector support Gatto et al, 2014). Irrespective of whether the smallholder adoption was sporadic or supported, oil palm was a novel crop and a livelihood option in the context of smallholder agriculture.…”
Section: Potential Impact Pathways Of Oil Palm Adoptionmentioning
confidence: 99%
“…The annual revenues of flowers, fruits, and nursery-grown plants were 6-12 × 10 4 yuan/ha, 6-7.5 × 10 4 yuan/ha and 1.5-3 × 10 4 yuan/ha, which were far higher than the annual revenue of 1500 yuan/ha of grain crops [17]. Other studies found that the choice of commercial crop farming is affected by household and individual characteristics, local and macro-economic factors, and land use policy [39,40]. For example, Kline found that land use law and urban growth boundaries had a significant inhibitory effect on the growth of non-agricultural land in western Oregon and western Washington in the USA [34].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Akibat perubahan tutupan dan pemanfaatan lahan tersebut pada akhirnya ekspansi perkebunan kelapa sawit mengubah sistem nafkah (livelihood system) masyarakat desa di sekitar perkebunan kelapa sawit (McCarthy, 2010;Rist, et al, 2010;Sayer, et al, 2012;Orsato et al, 2013;Lee, 2013;Gatto, et. al.,2015).…”
Section: Rumusan Masalahunclassified